2014
DOI: 10.3892/mmr.2014.2159
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside, a component of Centella asiatica, inhibits melanogenesis in B16F10 mouse melanoma

Abstract: Abstract. Melanogenesis is the process of generating pigmentation via melanin synthesis and delivery. Three key enzymes, tyrosinase, tyrosinase-related protein 1 (TRP1) and TRP2, metabolize melanin from L-tyrosine. Melanin synthesizing enzymes are regulated by microphthalmia-associated transcription factor (MITF). The titrated extract of Centella asiatica (TECA) contains the major components asiatic acid, asiaticoside and madecassic acid. The present study revealed that TECA reduces the melanin content in mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 18 publications
0
25
0
2
Order By: Relevance
“…Asiaticoside has a variety of biological actions including anti-inflammatory [37] and anti-hepatofibrotic effects [11], as well as serving as an inhibitor of melanogenesis [17], a neuroprotector against transient cerebral ischemia and reperfusion [7] and an inducer of apoptosis of tumor cells [1,15]. In particular, research has revealed that asiaticoside functioned effectively in preventing keloids and hypertrophic scars by suppressing the TGF-β1 induced expression of collagen [33].…”
Section: Introductionmentioning
confidence: 99%
“…Asiaticoside has a variety of biological actions including anti-inflammatory [37] and anti-hepatofibrotic effects [11], as well as serving as an inhibitor of melanogenesis [17], a neuroprotector against transient cerebral ischemia and reperfusion [7] and an inducer of apoptosis of tumor cells [1,15]. In particular, research has revealed that asiaticoside functioned effectively in preventing keloids and hypertrophic scars by suppressing the TGF-β1 induced expression of collagen [33].…”
Section: Introductionmentioning
confidence: 99%
“…During melanogenesis, melanin is produced from L-tyrosine by the key enzyme tyrosinase (Pillaiyar et al 2017;Kwon et al 2014;D'Mello et al 2016), and various skin-whitening raw materials have been developed to inhibit the expression and activity of tyrosinases (Gunia-Krzyżak et al 2016;Lee et al 2016;Choi et al 1998). The present study shows that C. chinensis extracts inhibit melanogenesis by decreasing tyrosinase activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It decreased the expression levels of focal adhesion kinase (FAK), and the probable mechanism of AA may be related to the inhibition of signal transduction mediated by FAK [21]. Asiatic acid, asiaticoside, and madecassic acid was the major composition of titrated extract of C. asiatica, and asiaticoside reduces melanogenesis in B16F10 mouse melanoma by checking tyrosinase mRNA expression [22]. In long-…”
Section: Anticancer Activitymentioning
confidence: 99%